Scaling of velocity profiles for depth-limited open channel flows over simulated rigid vegetation - Cheng, Nian-Sheng (2013)
Using the plane mixing layer analogy, a length scale is proposed to normalize velocity profiles for vegetated open channel flows. The new scaling is an improvement over those based on the logarithmic, velocity-defect, and power laws in collapsing the velocity profiles, which include measurements conducted in this study and also those reported in the literature for a variety of flow and vegetation configurations. An eddy viscosity model is also developed to justify the scaling argument. This study is limited to rigid vegetation submerged in depth-limited flows, in which the flow depth is no greater than twice the vegetation height.